Effect of Lactobacillus plantarum enriched with organic/inorganic selenium on the quality and microbial communities of fermented pickles. (15th December 2021) - Zhou, Mengzhou; Zheng, Xin; Zhu, Hanjian; Li, Leibing; Zhang, Lin; Liu, Menglin; Liu, Zeping; Peng, Mingye; Wang, Chao; Li, Qin; Li, Dongsheng
Highlights: Probiotic enriched in different selenium sources and fermented selenium-enriched pickle were prepared. The pH; antioxidant activities; the inhibition of advanced glycation end-products (AGEs); flavor components, and the contents of organic acids, free amino acids (FAAs), amino acid nitrogen (AAN), and nitrite were determined. The composition of microorganisms and the main differences in the microorganism composition among different groups were identified. The correlation between microorganisms, environmental factors and flavor substances was analyzed. Abstract: Lactobacillus enriched with organic/inorganic selenium and pickles fermented with the Lactobacillus plantarum R were prepared. The results showed that selenium-enriched Lactobacillus plantarum R enhanced the antioxidant capacity, inhibition rate of advanced glycation end-products (AGEs), nitrite degradation, and the organic acid production of fermented pickles, while Lactobacillus plantarum R enriched with inorganic selenium (R-Se-IN) showed the best performance. Twenty-three aroma-active substances and seven characteristic compounds were detected in the R-Se-IN group. Moreover, the bacterial community result revealed that Lactococcus, Lactobacillus, and Leuconostoc were predominant in the R-Se-IN group, while the other groups contained Enterobacter, Halomonas, and Klebsiella . Furthermore, the correlations between environmental factors, differential flavor substances, and microbial communities were explored based on multivariate statistical analysis. These results indicate that the addition of Lactobacillus plantarum R enriched with organic/inorganic selenium influenced the environmental factors, differential flavor substances, and microbial communities of the fermented pickles.